2020
DOI: 10.18311/jbc/2020/23164
|View full text |Cite
|
Sign up to set email alerts
|

Resource efficient and cost reduction technology for Trichogramma chilonis Ishii (Hymenoptera: Trichogrammatidae) production

Abstract: In India, the egg parasitoid Trichogramma chilonis Ishii is generally mass produced on the eggs of rice moth, Corcyra cephalonica Stainton, however, in the present study, the cost of production of T. chilonis was studied on Samia cynthia ricini, eri silkworm, and was compared with rice moth. Rearing of T. chilonis on eri silkworm eggs showed higher benefit cost-ratio of 1.89 with a net profit of Rs. 4620, whereas T. chilonis when reared on the eggs of C. cephalonica recorded a benefit cost ratio of 1.28, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The size of the host egg has been found to impact the oviposition and reproduction rate of Trichogramma females (Fournier & Boivin, 2000;Jin et al, 2021;Manisha et al, 2020).…”
Section: Mass Rearing and Storage Of Trichogrammamentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the host egg has been found to impact the oviposition and reproduction rate of Trichogramma females (Fournier & Boivin, 2000;Jin et al, 2021;Manisha et al, 2020).…”
Section: Mass Rearing and Storage Of Trichogrammamentioning
confidence: 99%
“…Eri silkworm, Philosamia ricini (Lepidoptera: Saturniidae), can be used as a host for producing T. chilonis. However, the mass production and maintenance of the host require providing it with castor leaves, collecting cocoons, and releasing the host into egg-laying cages for the emergence and collection of egg masses from egg-laying cages (Manisha et al, 2020). Whatever the rearing host or conditions, only Trichogramma with a high preference for S. frugiperda eggs can be applied for successful biocontrol (Smith, 1996).…”
Section: Mass Rearing and Storage Of Trichogrammamentioning
confidence: 99%
“…Assessments for other pests or in other countries indicated that a number of active ingredients were cost-effective, including capsaicin, Chromobacterium subtsugae, garlic extracts, Isaria fumosorosea, Metarhizium anisopliae, spinosad and Trichogramma spp. (Dougoud et al 2019, Kivett et al 2015, Manisha et al 2020, Nayak et al 2019).…”
Section: Affordabilitymentioning
confidence: 99%
“…For most of the biopesticide AI, there were no specific figures available on their cost and there was very little information on (Dougoud et al, 2019;Kivett et al, 2015;Manisha et al, 2020;Nayak et al, 2019).…”
Section: Affordabilitymentioning
confidence: 99%